The association between Dietary Oxidative Balance Score and muscle strength: NHANES 2011–2014 - Sun, Li; Xu, Changyu; Wang, Gang; Jin, Changming; Hu, Haoran; Liu, Yanyan; Li, Yang; Tang, Changhui; Hua, Qingli (Frontiers in Nutrition, 2025)
BackgroundDietary Oxidative Balance Score (DOBS) is an indicator, and on muscle strength remains largely unexplored in existing literature. We aimed to investigate the potential association between DOBS and muscle strength, and to explore possible interactions between DOBS and other covariates.MethodsThe association between DOBS and muscle strength under adjustment for confounders was analyzed using a weighted generalized linear regression model. A stratified analysis was used to conduct a sensitivity analysis of the linear regression.ResultsThe positive association between DOBS and muscle strength were found in this study. DOBS was positively associated with muscle strength only in the active activity subgroup. And the association between DOBS and muscle strength was stronger in the non-hypertensive group.ConclusionsDOBS and muscle strength showed an associated effect, and there was an interaction between DOBS with physical activity as well as hypertension, respectively. Individuals are encouraged to enhance DOBS levels. The findings may provide some potential theoretical references for the prevention of muscle strength loss through oxidative stress.